YOUTUBE “Satu Persen” SEBAGAI SARANA KOMUNIKASI MASSA PENGEMBANGAN DIRI MAHASISWA - Ervita Riliana; Nina Yuliana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
YouTube which is a means of mass communication, now has an impact on student self-development. YouTube